Postpartum Regression of a Presumed Cavernous Meningioma. (15th March 2016) - Phang, See Yung; Whitfield, Peter
Abstract : Meningiomas are known to be more common in females than males. They are also known in rare cases to grow in size during pregnancy, which can complicate its management. We describe a 31-year-old Caucasian woman who presented with blurring of her vision and diplopia during the third trimester of her pregnancy. Magnetic resonance imaging (MRI) showed a small left cavernous sinus meningioma. The patient was treated conservatively until her uncomplicated delivery. A postpartum MRI scan showed complete regression of the suspected meningioma. Currently the patient is contemplating a further pregnancy.